VARIATIONS IN THE RATE OF OXYGEN CONSUMPTION, AMMONIA EXCRETION AND O:N RATIO OF FRESHWATER BIVALVE, INDONAIA CAERULEUS (PRASHAD, 1918)IN RELATION TO BODY SIZE DURING SUMMER - A. N. VEDPATHAK,; R. J. MULEY,; D. T. TANGADE, (The Bioscan, 2011)
Considering the size specific variations in metabolic rates of bivalve shell-fishes we report here the size dependent variation in the O: N ratio in freshwater bivalve molluscs, Indonaia caeruleus from the banks of Godavari River at Paithan, near Aurangabad. The freshwater bivalves with specific size i.e. small (42-48mm in shell-length) and large (56-63 mm in shell-length) were selected for determination of changes in the rate of oxygen consumption, rate of ammonia excretion and O:N ratio on April and May during summer. The adult bivalves with small size, showed high values of O:N ratio (29.5547±3.7473) on April and (32.2309±3.2949) on May during summer compared to larger sized animals(20.5216±1.2097) on April and (17.5520±2.8302)on May. The values of O:N ratio were found to be greater in large sized bivalves on May during summer season. The results are discussed in the light of metabolic processes in fresh-water bivalve molluscs.